2022
DOI: 10.1200/jco.21.02592
|View full text |Cite
|
Sign up to set email alerts
|

Risk of COVID-19 Infections and of Severe Complications Among Survivors of Childhood, Adolescent, and Young Adult Cancer: A Population-Based Study in Ontario, Canada

Abstract: PURPOSE Survivors of childhood, adolescent, and young adult cancer are at risk of late effects, including pulmonary and infectious complications. Whether survivors are at increased risk of COVID-19 infection and severe complications is unknown. METHODS Population-based registries in Ontario, Canada, identified all 5-year survivors of childhood cancer diagnosed age 0-17 years between 1985 and 2014, and of six common adolescent and young adult cancers diagnosed age 15-21 years between 1992 and 2012. Each survivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…The results from the study by Gupta et al 1 have shown that young cancer survivors do not face a higher risk of COVID-19 disease as compared with the control group, which were established on the basis of demographic and medical characteristics such as age, income, and presence of various medical diagnosis. However, likewise mentioned in this study, a study by Cheung et al 2 concluded higher anxiety levels over COVID-19 disease among childhood cancer survivors and caretakers.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…The results from the study by Gupta et al 1 have shown that young cancer survivors do not face a higher risk of COVID-19 disease as compared with the control group, which were established on the basis of demographic and medical characteristics such as age, income, and presence of various medical diagnosis. However, likewise mentioned in this study, a study by Cheung et al 2 concluded higher anxiety levels over COVID-19 disease among childhood cancer survivors and caretakers.…”
Section: To the Editormentioning
confidence: 99%
“…In a recent study, Gupta et al 1 investigated the risk and severity of COVID-19 disease in young cancer survivors and concluded that young cancer survivors do not face higher risks or more severe complications of COVID-19 disease. We would like to congratulate the authors for this highly comprehensive study.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, the majority of global deaths from young-onset cancers occur in low-and middle-income countries, where the young population has poor access to health care. [4][5][6] Individuals with young-onset cancers have unique challenges and needs before, during, and after treatment, including delayed diagnosis, 7 poor treatment outcomes, 8,9 long-term complications, [10][11][12][13][14][15][16] difficult end-of-life care, 5 and significant loss of potential life. 17 Therefore, global efforts to prevent young-onset digestive tract cancers are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…While the risk of poor COVID-19 outcomes among long-term cancer survivors has not been elucidated, the concomitant risk factors due to pre-existing chronic medical conditions related to prior chemotherapy and radiation therapy (e.g., cardiomyopathy, coronary artery disease and pulmonary fibrosis, immunosuppression due to prior bone marrow transplant or splenectomy) are likely to place dual survivors at elevated risk. Interestingly, a recent study of childhood, adolescent and young adult survivors found no increase in risk for COVID-19 and severe complications (Gupta et al, 2022). Identifying and caring for such individuals will likely present further challenges as cancer survivors may also have pre-existing symptoms, such as neuropathy, musculoskeletal deconditioning, among others with resultant functional impairments that put them at higher risk for Long-COVID and related sequelae.…”
Section: Shared Pathophysiology and 'Dual Survivors'mentioning
confidence: 99%